Who Needs a Contractile Actomyosin Ring? The Plethora of Alternative Ways to Divide a Protozoan Parasite - Hammarton, Tansy C. (Frontiers in Cellular and Infection Microbiology, 2019)
Cytokinesis, or the division of the cytoplasm, following the end of mitosis or meiosis, is accomplished in animal cells, fungi and amoebae, by the constriction of an actomyosin contractile ring, comprising filamentous actin, myosin II and associated proteins. However, despite this being the best-studied mode of cytokinesis, it is restricted to the Opisthokonta and Amoebozoa, since members of other evolutionary supergroups lack myosin II and must, therefore, employ different mechanisms. In particular, parasitic protozoa, many of which cause significant morbidity and mortality in humans and animals as well as considerable economic losses, employ a wide diversity of mechanisms to divide, few, if any, of which involve myosin II. In some cases, cell division is not only myosin II-independent, but actin-independent too. Mechanisms employed range from primitive mechanical cell rupture (cytofission), to motility- and/or microtubule remodelling-dependent mechanisms, to budding involving the constriction of divergent contractile rings, to hijacking host cell division machinery, with some species able to utilise multiple mechanisms. Here, I review current knowledge of cytokinesis mechanisms and their molecular control in mammalian-infective parasitic protozoa from the Excavata, Alveolata and Amoebozoa supergroups, highlighting their often-underappreciated diversity and complexity. Billions of people and animals across the world are at risk from these pathogens, for which vaccines and/or optimal treatments are often not available. Exploiting the divergent cell division machinery in these parasites may provide new avenues for the treatment of protozoal disease.